Effect Of Inbreeding And Some Other Factors On Breeding Efficiency In Gir Cows - Tomar, S. S.; Kumar , Amit; Sharma , Harish (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Effects of period and season of first calving, sire and inbreeding on breeding efficiency by Wilcox (BEW) and Tomar (BET) methods were studied on 188 Gir cows maintained at the Kasturba Gandhi National Memorial Trust Dairy farm, Kasturbagram, Indore (M.P.). The least squares means of BEW and BET were found to be 79.29±1.10 and 67.12±0.85 per cent, respectively. Significant effect of sire (P<0.05) and inbreeding (P<0.01) were found on both the breeding efficiencies while period and season had non-significant effect. Inbred cows had significantly lower breeding efficiency in comparison to non-inbred cows. From the observations it could be concluded that inbreeding had deteriorating effect on breeding efficiency.